Growth and quality of Chlorella vulgaris and Chaetoceros calcitrans in photobioreactors using low cost media formulated from fertiliser - Silva, Alexander Zachariah De (2019)
Microalgae are gaining interest by numerous industries such as the aquaculture, health sciences and pharmaceutical. However, microalgae cultivation is constantly linked to high investment due to the cost of culture media. Therefore, formulation of low-cost media for high quality microalgae cultivation would increase the interest of microalgae usage in many industries. The current study aims to formulate a simple and cost-effective media for the cultivation of Chlorella vulgaris and Chaetoceros calcitrans. Locally available common fertiliser ‘Serbajadi 63’ containing 21:21:21 of nitrogen: phosphorus: potassium and ‘Serbajadi 46’ containing 46% of urea were used as the base formulae for the study.